The great reversal how America gave up on free markets - Philippon, Thomas (The Belknap Press of Harvard University Press, 2019)
"American markets, once a model for the world, are giving up on competition. Thomas Philippon blames the unchecked efforts of corporate lobbyists. Instead of earning profits by investing and innovating, powerful firms use political pressure to secure their advantages. The result is less efficient markets, leading to higher prices and lower wages"--